Creating an equitable and inclusive STEM classroom: a qualitative meta-synthesis of approaches and practices in higher education - Duncan, Victoria L.; Holt, Emily A.; Keenan, Susan M. (Frontiers in Education, 2023)
How can Science, Technology, Engineering, and Mathematics (STEM) faculty integrate a humanistic approach to create environments where students do not feel marginalized? Changes are necessary to address the historically exclusive climate and systemic oppressive classroom policies and classroom practices dominated by White, patriarchal, Eurocentric perspectives pervasive in many STEM higher education classrooms. By incorporating approaches and practices documented in the literature over time and across multiple STEM disciplines, faculty can create equitable and inclusive (EI) classrooms. However, the challenge for individual faculty members is consolidating the information to identify fundamental elements necessary for establishing EI spaces. This project addresses that challenge by conducting a comprehensive meta-synthesis of higher education literature to identify themes for what constitutes an EI classroom and recommendations for how faculty can facilitate one. The dataset includes 61 articles from 277 authors and 48 unique journals and reflects a timeframe of January 1995-June 2021. Our findings are organized into four key concepts, indicating that EI pedagogies related to the affective, cognitive, and metacognitive categories of learning are vital to an equitable and inclusive classroom. However, the essential finding of this analysis was the importance of the fourth key concept, faculty cultural competency and elements related to the climate and structure of the classroom, referred to as Faculty Agency and Actions (FAA) The results of this metasynthesis were compared to the most frequently cited seminal works within the field, demonstrating that although these individual works contain most, they do not include all of the themes indicated by this study and, in some cases, over-or underrepresent some of the topics discussed. As mirrored in the most frequently cited works and the findings of this meta-synthesis, it takes incorporating classroom-focused approaches and faculty's reflective resolve to understand and change how dominant and privileged identities are reflected for classrooms to be equitable and inclusive in STEM.